2022
DOI: 10.1149/1945-7111/ac8d2f
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Catalytic Activity of Bifunctional Cobalt Boride Nanoflakes for Overall Water Splitting over a Wide pH Range

Abstract: The world is in the process of transitioning toward a more sustainable energy future, with green hydrogen considered an attractive energy vector that can replace fossil fuel consumption, meeting global energy demands. To date, the most advanced method to produce green hydrogen is through water electrolysis using the residual supply of renewable energy. The current state-of-the-art catalysts used in electrolyzers are platinum-based metals and ruthenium/iridium oxides. The scarceness of these elements, combined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…5b) exhibits two peaks, with the first located at ∼192 eV assigned to boron nickel interactions (B–N), 21,34,39 and the second at ∼198.9 eV related to boron oxo species. 9,10,40 On the other hand, for the NiB/NiBO 3 -II and NiB/NiBO 3 -III samples, the second boron peak of their B 1s spectra (Fig. 5e and h) was further deconvoluted to two more peaks, centred at ∼198.2 eV and ∼199.8 eV, indicating that the extra available boron during synthesis was further oxidised to B 2 O 3 .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…5b) exhibits two peaks, with the first located at ∼192 eV assigned to boron nickel interactions (B–N), 21,34,39 and the second at ∼198.9 eV related to boron oxo species. 9,10,40 On the other hand, for the NiB/NiBO 3 -II and NiB/NiBO 3 -III samples, the second boron peak of their B 1s spectra (Fig. 5e and h) was further deconvoluted to two more peaks, centred at ∼198.2 eV and ∼199.8 eV, indicating that the extra available boron during synthesis was further oxidised to B 2 O 3 .…”
Section: Resultsmentioning
confidence: 98%
“…1–3 This significant traction of 2D nanomaterials can be attributed to their outstanding properties like their high specific surface area, significant carrier mobility, 4,5 high electrical conductivity, 6,7 and most importantly, materials versatility since they can be crystalline or amorphous, as well as organic or inorganic. 8 Despite these outstanding properties, 2D nanomaterials still need additional tuning in order to accommodate the needs of their potential application, such as catalysis, 9,10 energy storage 11 or optoelectronics. 12 This tuning can be easily achieved by assembling different 2D nanomaterials into heterostructures, in other words, creating a hybrid system that presents an interface between two materials.…”
Section: Introductionmentioning
confidence: 99%
“…Around this problem, a series of Fe–B, Fe–S, Fe–P and other catalytic materials have been reported; 7,8 Ghafar et al reviewed the research progress of electrocatalytic water splitting of metal borate. 9 Among them, Fe–B catalytic materials have achieved the advantages of efficient catalysis, mild reaction conditions, non-toxicity, and few by-products and have received great attention in the field of efficient water splitting. 10 Gao et al introduced carbon nanotubes (CNTs), prepared CNTs modified with FeB nanoparticles (expressed as FeB/CNTs) into the MgH 2 system by cyclohexane (CYH) wet grinding, and the results showed that both CYH and the addition of dopants (CNT, FeB or FeB/CNT) could improve the catalytic effect.…”
Section: Introductionmentioning
confidence: 99%
“…They have high melting points and hardness, they are thermodynamically stable, they have excellent electric conductivity and superconductivity, and they are catalytically active and corrosive resistant [ 1 , 2 , 3 , 4 ]. Hence, they are extensively used in sensing, electronics, catalysis, energy harvesting, ion transport, superconductivity, hydrogen generation, and storage [ 5 , 6 , 7 , 8 , 9 ]. Their stoichiometry varies from compounds with low a boron content similar to metal mono-borides (MB) to compounds with a very high boron content (MB 99 ).…”
Section: Introductionmentioning
confidence: 99%